The metabolic roles of free amino acids during seed development. (October 2018) - Amir, Rachel; Galili, Gad; Cohen, Hagai
Highlights: Amino acids play pivotal roles in seeds during their development. The pools of free and total amino acids vary in different stages of seed development. The biosynthetic pathways of amino acids in seeds are tightly regulated by metabolic networks. Altered levels of amino acids can greatly affect seed physiology and behavior. Abstract: Amino acids play vital roles in the central metabolism of seeds. They are primarily utilized for the synthesis of seed-storage proteins, but also serve as precursors for the biosynthesis of secondary metabolites and as a source of energy. Here, we aimed at describing the knowledge accumulated in recent years describing the changes occurring in the contents of free amino acids (FAAs) during seed development. Since several essential amino acids are found in low levels in seeds ( e.g., Lys, Met, Thr, Val, Leu, Ile and His), or play unique functional roles in seed development ( e.g ., Pro and the non-proteinogenic γ-aminobutyrate [GABA]), we also briefly describe studies carried out in order to alter their levels in seeds and determine the effects of the manipulation on seed biology. The lion share of these studies highlights strong positive correlations between the biosynthetic pathways of FAAs, meaning that when the levels of a certain amino acid change in seeds, the contents of other FAAs tend to elevate as well. These observations infer a tight regulatory network operating in the biosynthesis of FAAs during seed development.